The Enhanced Brief Structured Observation Model: Efficiently Assess Trainee Competence and Provide Feedback - Scott Baumgartner; Dewesh Agrawal; Larrie Greenberg (Association of American Medical Colleges, 2021)
Introduction The regular observation of trainees is essential to ascertain trainee proficiency in competency-based assessments. Unfortunately, observation of residents is not frequent enough to facilitate entrustment decisions, and the busy clinician-educator may not have the tools or time to conduct effective and efficient observations. Methods We created a hands-on faculty development workshop utilizing an enhanced variation of the brief structured observation (BSO) technique to train both primary care and subspecialty pediatric faculty on how to effectively and efficiently observe trainees. The workshop has provided faculty a practical approach to observing trainees in a focused fashion and providing effective feedback on clinical skills based on their observation. In the workshop, faculty had an opportunity to observe residents taking an unrehearsed history from a medical student simulating an acutely ill patient, culminating in feedback on the residents' performance using the subjective, objective, assessment, and plan (SOAP) format. Results This faculty development workshop has been presented to more than 100 faculty both locally and nationally, and feedback has been uniformly positive, with three institutions incorporating this model into their programs to date. Discussion This enhanced BSO workshop promotes a model that streamlines the observations of trainees and provides faculty with the tools to encourage more observations.